2021
DOI: 10.3390/diagnostics11112163
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Algorithm Using Cell Population Data (VCS Parameters) as a Screening Discriminant between Alpha and Beta Thalassemia Traits

Abstract: Thalassemia is one of the major inherited haematological disorders in the Southeast Asia region. This study explored the potential utility of red blood cell (RBC) parameters and reticulocyte cell population data (CPD) parameters in the differential diagnosis of α and β-thalassaemia traits as a rapid and cost-effective tool for screening of thalassemia traits. In this study, a total of 1597 subjects (1394 apparently healthy subjects, 155 subjects with α-thalassaemia trait, and 48 subjects with β-thalassaemia tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This could discriminate the α from the β ‐thalassemia trait. The respective sensitivity and specificity values were 92% and 90%, with the AUC value reaching 0.97 with a cut‐off value of 1742.5 [66]. CPD deserves further exploration for potential clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…This could discriminate the α from the β ‐thalassemia trait. The respective sensitivity and specificity values were 92% and 90%, with the AUC value reaching 0.97 with a cut‐off value of 1742.5 [66]. CPD deserves further exploration for potential clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 10 hematological parameters of TT and IDA in this study were statistically different, considering the current laboratory blood cell detection methods, only RBC, Hb, and HCT are the measurement results, while MCV, MCH, MCHC, RDW-CV are calculated from the previous values. And some studies have found that MCV does not accurately reflect erythropoiesis [ 49 ]. In any progressive iron depletion, the latest red blood cell volume is the smallest, while thalassemia is not iron deficient, so its red blood cell MCV does not change It has also been found that MCV is not a good indicator to distinguish TT from IDA [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, a model was described associating some indices of red blood cells with Hb A 2 levels to differentiate β-thalassemia, α-thalassemia, and iron deficiency [ 31 ]. An algorithm has been developed to differentiate between α-thalassemia and β-thalassemia traits (αβ-algorithm), especially in geographic regions with large numbers of individuals with these inherited blood disorders [ 32 ].…”
Section: Discussionmentioning
confidence: 99%